MENGUKUR KUALITAS KINERJA PELAYANAN PUBLIK (PROGRAM JAMINAN KESEHATAN NASIONAL) DENGAN SURVEY KEPUASAN PASIEN - Moh. Wildan; Hary Yuswadi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2015)
One effort to increase the quality of public services, as mandated in the Law of the Republic of Indonesia number 25 year 2000 concerning the National Development Program (PROPENAS), needs to be amonged community satisfaction index as a benchmark to assess the level of quality of service. This paper intend to describe and analyze some models and theories of public service performance measurement that related to the implementation of the National Health Insurance program (JKN) held by BPJS-of Health. Health care quality is measured from the aspect of community/patient satisfaction survey. Then linked with efforts to increase patient loyalty towards the implementation of the program JKN. The implications of this paper is expected to formulate an instrument and indicators valid, reliable and comprehensive to measure the quality of health services JKN program. Optimal patient satisfaction is expected to make loyal patients to use health services with JKN program and recommend to others to follow JKN program